Maternal risk factors and meconium stained amniotic fluid - Bhinder, Onkar S.; Singh, Gurmeet; Thapar, Karuna; Nain, Priyanshu (International Journal of Contemporary Pediatrics, 2022)
Background: Meconium is a sterile, thick, black-green, odourless material that results from accumulation of debris in fetal intestine during the third month of gestation. The risk factors for meconium-stained amniotic fluid (MSAF) are both maternal and fetal. MSAF is associated with higher rate of caesarean delivery, increased need for neonatal resuscitation and meconium aspiration syndrome. This observational study was undertaken so that such expecting mothers can be screened at an early stage and prompt intervention can be done to minimize neonatal morbidity and mortality. Methods: This prospective observational study was conducted in department of paediatrics of Sri Guru Ram Das University from December 2014 to June 2016 included all deliveries with meconium stained amniotic fluid excluding Twins, neonates with congenital malformations, multi organ dysfunction or requiring surgical intervention. Results: The incidence of MSAF was 3.42% with 10.5% mortality. Various maternal factors including multiparity, bad obstetric history, pregnancy-induced hypertension (PIH), intrauterine growth restriction (IUGR), maternal diabetes, anaemia and non-reassuring cardiotocography (CTG) record were found to be statistically important and associated with poor outcome. Conclusions: MSAF and poor neonatal outcome is related to antenatal care. Thus, good antenatal and perinatal care can prevent morbidity and mortality in neonate by early identification of signs of fetal distress and passage of meconium inutero and improve outcome.